Big data analytics capabilities (BDAC) and sustainability reporting on Facebook: Does tone at the top matter? - Fareyha Said; Dalilawati Zainal; Azlina Abdul Jalil (Cogent Business & Management, 2023)
This study examines the impact of big data analytics capabilities (BDAC) on sustainability reporting disclosure on Facebook (SRDF) and the moderating impact of tone at the top's attributes on the relationship between BDAC and SRDF. A total of 100 publicly listed companies (PLCs) in Malaysia that mentioned using social media during the year 2019 were chosen as this study's sample. This study was underpinned by positivist research paradigm and used quantitative data collection methods (questionnaire and content analysis). Based on the structural equation modelling (SEM) employed, the results of the study showed that BDAC implementation had a significant impact on SRDF. The presence of a specific tone (certainty) at the top in Chief Executive Officer's (CEO) letters strengthened the relationship between BDAC and SRDF, but other attributes of tone at the top showed insignificant results. This study acknowledges the important contribution of dynamic capabilities, such as BDAC and a specific tone at the top, i.e., certainty, in promoting sustainability reporting on social media from the perspective of dynamic capabilities view (DCV) theory. Thus, companies are suggested to implement BDAC and communicate certainty in the tone at the top to improve their sustainability reporting on social media, particularly on Facebook.
Keywords: 650; Facebook; big data analytics capabilities; dynamic capability view; sustainability reporting; tone at the top